2019
DOI: 10.1186/s12887-019-1643-z
|View full text |Cite
|
Sign up to set email alerts
|

Imperforate anus associated with anomalous pulmonary venous return in scimitar syndrome. Case report from a tertiary hospital in Ethiopia

Abstract: Background Scimitar syndrome is a rare form of partial anomalous pulmonary venous drainage associated with pulmonary hypertension and congestive heart failure that may lead to death in the newborn infant. Although it is described with anomalies of the lung, heart and their vascular structure, extremely rare association with imperforate anus had been reported. The third case of Scimitar syndrome and imperforate anus will be reported in this case report. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[3][4][5][6][7][8][9] Studies have demonstrated an association between scimitar syndrome and extracardiac anomalies including congenital diaphragmatic hernia, imperforate anus, and variants of VACTERL association. [10][11][12][13][14] Although pathogenic variants in specific genes can clearly cause CHDs, the genetic factors contributing to most cases of scimitar syndrome remain unidentified. [3][4][5][6][7][8][9] In this study, we sought to determine the frequency and efficacy of genetic testing in patients with scimitar syndrome from a single institution.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Studies have demonstrated an association between scimitar syndrome and extracardiac anomalies including congenital diaphragmatic hernia, imperforate anus, and variants of VACTERL association. [10][11][12][13][14] Although pathogenic variants in specific genes can clearly cause CHDs, the genetic factors contributing to most cases of scimitar syndrome remain unidentified. [3][4][5][6][7][8][9] In this study, we sought to determine the frequency and efficacy of genetic testing in patients with scimitar syndrome from a single institution.…”
mentioning
confidence: 99%
“…However, other unusual presentations like congenital hydrocephalus, heart block, and imperforate anus associated with infantile scimitar have been reported in the literature. 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…Embolization of the aortopulmonary collaterals can also be done by detachable coils [11]. During our literature search, we came across other case reports of scimitar syndrome associated with other congenital defects such as VACTERL, H-type tracheoesophageal fistula [5,12], and imperforated anus [13]. We also came across case reports showing features of failure to thrive due to recurrent chest infections, leading to immediate repair of the defect.…”
Section: Discussionmentioning
confidence: 99%